2015
DOI: 10.1186/s40623-015-0364-2
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and validation of Mars ionospheric electron density profiles from Mariner 9

Abstract: Electron density profiles from the ionosphere of Mars that were obtained by the Mariner 9 radio occultation experiment in 1971-1972 have unique scientific value because they extend to higher altitudes than comparable datasets and were acquired during a tremendous dust storm that had substantial and poorly understood effects on the ionosphere. Yet these profiles are not publicly available in an accessible format. Here, we describe the recovery of these profiles, which are made available as part of this article.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 49 publications
(98 reference statements)
0
12
0
Order By: Relevance
“…In this season, as Mars approaches the Sun, increased solar irradiance and temperatures lead to a warmer and more circulated Martian atmosphere, which then lifts dust off the surface of Mars and causes the so-called dust storms. These dust storms have been previously shown to interact with the upper atmosphere and ionosphere of Mars in various ways, including the possibility of modulating the neutral densities and TEC [e.g., Wang and Nielsen, 2004;Mouginot et al, 2008;Liemohn et al, 2012;Withers, 2009;Withers and Pratt, 2013;Withers et al, 2015;Xu et al, 2014;Haider et al, 2015;Němec et al, 2015]. However, we do not draw any further conclusions on how the dust storms could directly impact the location of the Martian bow shock and leave such an investigation to a future study.…”
Section: Discussionmentioning
confidence: 86%
“…In this season, as Mars approaches the Sun, increased solar irradiance and temperatures lead to a warmer and more circulated Martian atmosphere, which then lifts dust off the surface of Mars and causes the so-called dust storms. These dust storms have been previously shown to interact with the upper atmosphere and ionosphere of Mars in various ways, including the possibility of modulating the neutral densities and TEC [e.g., Wang and Nielsen, 2004;Mouginot et al, 2008;Liemohn et al, 2012;Withers, 2009;Withers and Pratt, 2013;Withers et al, 2015;Xu et al, 2014;Haider et al, 2015;Němec et al, 2015]. However, we do not draw any further conclusions on how the dust storms could directly impact the location of the Martian bow shock and leave such an investigation to a future study.…”
Section: Discussionmentioning
confidence: 86%
“…This produces a thermal expansion of the lower atmosphere that is also observed in the upper atmosphere and as a consequence produces an increase in the altitude of the ionospheric peak (e.g., Hantsch & Bauer, ). Furthermore, Withers et al () recently reanalyzed the Mariner 9 radio‐occultation profiles that were recorded during a severe global dust storm (Kliore et al, ) and found a similar result; the ionosphere was systematically lifted upward by 20–30 km, although the peak density of the ionosphere was not affected. These observations suggest that while the ionosphere/thermosphere system was only moved upward, the total electron/ion column density, the TEC, was not affected.…”
Section: Discussion: Can Tec Be Considered As a Diagnostic Tool For Tmentioning
confidence: 89%
“…First, radio occultation experiments can be used to derive electron density profiles, that is, electron densities as a function of the altitude, spanning the altitudes both below and above the peak altitude. These were performed using the Mariner 9 spacecraft (Kliore et al, , ; Withers, Weiner, et al, ), Mars Global Surveyor spacecraft (Hinson et al, ), Mars Express spacecraft (Grandin et al, ; Pätzold et al, ), and recently using the Mars Atmosphere and Volatile EvolutioN (MAVEN) spacecraft (Withers et al, ). The main disadvantage of these profiles is that their spatial coverage is restricted by geometric constraints imposed by the orbits of Earth and Mars (Tyler et al, ; Withers et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…First, radio occultation experiments can be used to derive electron density profiles, that is, electron densities as a function of the altitude, spanning the altitudes both below and above the peak altitude. These were performed using the Mariner 9 spacecraft (Kliore et al, 1972a(Kliore et al, , 1972bWithers, Weiner, et al, 2015), Mars Global Surveyor spacecraft (Hinson et al, The second possible type of measurements is direct in situ measurements of electron/ion densities. Historically, a couple of such profiles was obtained by Viking 1 and 2 landers (Hanson & Zuccaro, 1977).…”
Section: Introductionmentioning
confidence: 99%